2023
DOI: 10.3389/fcell.2023.1013721
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed actin cap as a new personalized biomarker in primary fibroblasts of Huntington’s disease patients

Abstract: Primary fibroblasts from patient’s skin biopsies are directly isolated without any alteration in the genome, retaining in culture conditions their endogenous cellular characteristics and biochemical properties. The aim of this study was to identify a distinctive cell phenotype for potential drug evaluation in fibroblasts from Huntington’s Disease (HD) patients, using image-based high content analysis. We show that HD fibroblasts have a distinctive nuclear morphology associated with a nuclear actin cap deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Similar to exploring common variant associations, we are likely underpowered in any single disease category to identify significant associations. There have been many studies elucidating morphological features associated with various diseases, but they often contained larger sample sizes and incorporated more specialized cell types 22 , 65 , 66 . Extending our current study to diverse cell types and increasing the number of samples for clinical disease categories will be a critical next step in efforts to link cell morphology to human illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to exploring common variant associations, we are likely underpowered in any single disease category to identify significant associations. There have been many studies elucidating morphological features associated with various diseases, but they often contained larger sample sizes and incorporated more specialized cell types 22 , 65 , 66 . Extending our current study to diverse cell types and increasing the number of samples for clinical disease categories will be a critical next step in efforts to link cell morphology to human illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Over 100 interactions between huntingtin and different proteins are known [ 57 ]. The abnormal morphology of the HD fibroblast is correlated with actin cap deficiency, and it was suggested that this unique feature can be used as a personalized biomarker of HD [ 58 ]. The Rho-Rac GTPase cascade was identified to be involved in the reorganization of the cytoskeleton by actin-binding proteins cofilin and profilin, and it was concluded that the loss of phosphoSer138 in profilin is correlated with the symptomatic course of HD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells comprise a neuroblastoma cell line and are commonly utilised in HD research [21,22]. Reduced cell proliferation and altered nuclear morphology have been noted in HD post mortem brains previously [25]. Furthermore, in HD patients, mutant and wild-type HTT proteins are found to be nuclear-localised, which is largely thought to be due to the propensity of mutant HTT to be highly promiscuous and bind various proteins, including the nuclear master regulator REST within the cytoplasm [32].…”
Section: Discussionmentioning
confidence: 99%
“…As changes in nuclear and cell morphology have been noted in HD [24,25], these same parameters were also investigated in circHTT(2-6) overexpression cell lines. This was achieved through high-content imaging using an Operetta CLS (Perkin Elmer).…”
Section: Cell Morphology Analysismentioning
confidence: 99%